Effect of magnetic field locations on thermo-magnetic convection performance of Fe3O4/H2O ferrofluid flowing in a novel dimpled tube: An experimental study - Gürsoy, Emrehan; Gürdal, Mehmet; Kadir Pazarlıoğlu, Hayati; Dağdeviren, Abdullah; Tekir, Mutlu; Arslan, Kamil; Gedik, Engin; Adriana Minea, Alina; Kurt, Hüseyin (Elsevier BV, 2023)
The aim of this study is to examine the hydrothermal behavior of Fe3O4 Ferrofluid flowing under the effect of uniform magnetic field (0 T ≤ B ≤ 0.3 T). In addition, magnetic field locations were changed for each experiment to observe effect of the magnetic field locations (x/D = 20, 40, 60) on the hydrothermal behavior of the proposed system. Fe3O4 Ferrofluid was prepared in φ = 1.0% volume concentration in water and flows under the laminar regime (1131 ≤ Re ≤ 2102). Comparisons of the hydrothermal behavior of the novel proposed parameters were performed according to combinations of the different magnetic field locations and magnitudes. It is concluded that the highest Nusselt number was obtained using B = 0.3 T for the magnetic field location of x/D = 20 for both in smooth and dimpled tubes. Compared to B = 0 T, the Nusselt number enhancement was detected by 64.03% for smooth tube for the magnetic field location of x/D = 20 for B = 0.3 T whereas Nusselt number wasaugmented by 45.40% for dimpled tube for the same input parameters. Furthermore, no considerable changes in friction factor was determined under magnetic field effect when the application of magnetic field locations was changed. As a result of these findings, the highest increase in Performance Evaluation Criteria belonging dimpled tube was calculated by 33.54% at Re = 2102 for B = 0.16 T for the magnetic field location of x/D = 20. As a general conclusion, this study can shed light on investigating ferrofluids behavior under magnetic field applied in variable magnetic field locations.